KRISIS EKONOMI, DAYA TAHAN PENDUDUK, DAN SOCIAL SECURITY: KASUS JATINOM DI JAWA TENGAH - Irwan Abdullah (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1999)
The economic crisis that has been going on since 1997 has had different consequences in various areas. These differences have also provoked a series of discussions about whether or not there is indeed any impact from this crisis, or how far of this impact can be observed. By looking at the case of Jatinom, this study indicates that a community that does not suffer the impact of the crisis is mainly because of the supportive nature of the local resources. This includes the elastic nature of the agricultural sector and self-reliance of the community, which is manifested through a series of strategies that have been historically developed. The communal perception and reaction of Jatinom community towards the crisis is indeed a reflection of their elastic- optimistic attitude. They never portray an attitude of just being on the receiving side. They are instead preoccupied with productive economic activities, which are based on calculative considerations. This paper also emphasizes that the crisis should actually be looked at from a historical perspective in order to have a more detailed and contextual understanding about the impact of the crisis.